Gastrointestinal manifestations and pathogenesis in childhood immunoglobulin A vasculitis - Kato, Seiichi; Gold, Benjamin D.; Kato, Ayumu (Frontiers in Pediatrics, 2024)
Immunoglobulin A vasculitis (IgAV), previously known as Henoch-Schönlein purpura, is the most common form of systemic vasculitis in childhood. The primary organs involved are the skin, gastrointestinal (GI) tract, joints, and kidneys. The spectrum of GI involvement in IgAV ranges from being mild and self-limited to severe manifestations often requiring surgical intervention. Galactose-deficient IgA1 on the immunoglobulin hinge region and its immune complexes are thought to play a central pathogenetic role in IgAV, however, an association between such molecules and specific GI mucosal damage remains unclear. GI endoscopy (both upper and lower) shows a variety of mucosal findings, many of which are not specific for IgAV. In upper GI endoscopy, however, the mucosal features can be diagnostic when found localized in the more distal part of upper GI tract (second and/or third parts of the duodenum). Abdominal computed tomography and capsule endoscopy have demonstrated that the small intestine is most commonly involved in IgAV. The GI mucosal involvement when evaluated microscopically shows IgA deposition which is histologically diagnostic. Conversely, leukocytoclastic vasculitis is less useful. Since the 1960s, cases of duodenojejunitis, in which IgAV was suspected but evident purpura was not dermatologically present, have often been labeled as “idiopathic”. In a pediatric case series, IgA enteropathy, without dermatological manifestations (i.e., purpura), was reported to have similar symptoms, as well as endoscopic characteristics and immunohistological findings as in IgAV. Subsequently, several case reports provide additional supportive evidence that IgA enteropathy must be a variant of IgAV. Thus, the immunologically driven auto-immune vasculitis results in the symptom complex dependent on the organ system involved, and the subsequent clinical features which are manifested. Present classification criteria are useful and universally available for diagnosing IgAV. However, based upon current knowledge including IgA enteropathy, minor modification of the IgAV criteria is proposed in the review.